2019
DOI: 10.1049/iet-rpg.2018.5134
|View full text |Cite
|
Sign up to set email alerts
|

CFD study of blockage ratio and boundary proximity effects on the performance of a tidal turbine

Abstract: The effects of blockage ratio and boundary proximity on tidal turbine performance are quantified in this study using computational fluid dynamics (CFD). Reynold averaged Navier-Stokes (RANS) equations are solved using the commercial CFD code ANSYS CFX. Steady-state analyses are performed using a rotating frame of reference technique, and a shear stress transport turbulence model is used. Results from the numerical model are validated with experimental data. RANS CFD simulations are performed over tip speed rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The C-shaped computational domain boundaries are located at 13 chord lengths in front, above, and below the aerofoil, and 25 chord lengths behind. The boundaries perpendicular to the flow can generate a blockage ratio of around 2% according to past research (e.g., Badshah et al [12]). In the present work, it was found that when blockage is below 10% there is little or no effect on results, but when blockage increases above 10%, rapid changes in results occur.…”
Section: Geometry and Computational Domainmentioning
confidence: 87%
See 1 more Smart Citation
“…The C-shaped computational domain boundaries are located at 13 chord lengths in front, above, and below the aerofoil, and 25 chord lengths behind. The boundaries perpendicular to the flow can generate a blockage ratio of around 2% according to past research (e.g., Badshah et al [12]). In the present work, it was found that when blockage is below 10% there is little or no effect on results, but when blockage increases above 10%, rapid changes in results occur.…”
Section: Geometry and Computational Domainmentioning
confidence: 87%
“…The boundary conditions used for the flow domain were as follows: the front and bottom boundaries were set as velocity inlets with specified velocity components and standard mean sea level values for pressure and temperature; turbulent intensity was set at 0.25% (similar to what was used by Jawahar et al [4]); solid The C-shaped computational domain boundaries are located at 13 chord lengths in front, above, and below the aerofoil, and 25 chord lengths behind. The boundaries perpendicular to the flow can generate a blockage ratio of around 2% according to past research (e.g., Badshah et al [12]). In the present work, it was found that when blockage is below 10% there is little or no effect on results, but when blockage increases above 10%, rapid changes in results occur.…”
Section: Geometry and Computational Domainmentioning
confidence: 87%
“…The finite volume method integrated inside ANSYS CFX is used to carry out the numerical simulations. The unsteady Reynolds-Averaged Navier-Stokes (URANS) equation is closed by the two-equation shear stress transport (SST k-ω) model [27][28][29] with automatic near-wall treatment that automatically switches from wall-functions to a low-Re near-wall formulation as the mesh is refined. The SST k-ω turbulence model has been embedded into the commercial code ANSYS CFX and, thus, is convenient to be selected to carry out the simulations in this study.…”
Section: Numerical Schemes and Boundary Conditionsmentioning
confidence: 99%
“…This model has the capability of gradually changing from the standard K − ω model in the inner region of the boundary layer flow to a high Reynolds-number version of the K − ε model in the outer part of the boundary layer so that advantages of both models can be utilized. The SST model is known to predict the onset and amount of flow separation under adverse pressure gradient with better convergence [42] and has been successfully used to model the near wake of tidal turbines [43][44][45]. An SST model with automatic wall function is also utilized for the work presented in this paper.…”
Section: Computational Fluid Dynamics Modelmentioning
confidence: 99%